A percepção e a atuação de aprendizes em relação à autonomia em um curso de inglês para propósitos acadêmicos no contexto do programa Idiomas sem Fronteiras - Della Rosa, Stefanie Fernanda Pistoni (2018)
This study aims at analyzing learners’ attitudes and perceptions regarding autonomy in an English for Academic Purposes (EAP) course, focused on writing skills (academic writing), based on the comprehension of their roles and responsibilities, as well as roles and responsibilities of teachers and teaching materials. Such comprehension is imperative when the development of autonomy beyond classroom is considered within the language learning-teaching process, mainly when active engagement in a discourse community is intended by such learner-researcher. For this reason, this research is based on studies about English for Specific Purposes (ROBINSON, 1991; HUTCHINSON e WATERS, 2006; DUDLEY-EVANS e ST. JOHN, 2010) and its subarea English for Academic Purposes (FLOWERDEW e PEACOCK, 2001, HYLAND, 2006; JORDAN, 2012), as well as on theories of Autonomy (BENSON, 2006; 2011) e (LITTLE, 1991; 1995) and Teaching Materials (TOMLINSON, 2012, 2014; HARWOOD 2005, 2010, 2014; RICHARDS 2001, 2014). The methodological perspective is the case study, guided by the qualitative approach of research whose data was collected through semistructured questionnaires, class observation and interviews. The data was collected in an Academic Writing English course offered by the program Languages without Borders in one of its affiliated universities. The data analysis reveals that in order to foster learners’ autonomy in English for Academic Purposes courses collaborative work between teachers and learners is necessary, suggesting the redefinition of their roles, highlighting: i) learners’ control over their responsibilities in the teaching-learning process through their active engagement and reflection over such process and ii) teaching practice guided by both orientation and learners’ inclusion in the decision-making process. The results indicate the relevance of courses of English for Academic Purposes to aim at raising awareness towards both academic genre and discourse community, focusing on learners’ reflection of informed use of the language in order to reach any communicative purpose shared among the discourse community; as well as the consideration of teaching materials as a relevant resource to foster learners’ autonomy. For future studies we emphasize the need for more attention to teacher’s autonomy, since their initial education, because of the intrinsic relation between teachers’ autonomy and learners’ autonomy.